Pembuatan Kertas pH dari Bahan Alam (Bunga) Sebagai Alternatif Pengganti Indikator Sintetis Di MGMP Kimia Kabupaten Donggala - Puspitasari, Dwi Juli; Sosidi, Husain; Prismawiryanti, Prismawiryanti (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The lack of learning resources, especially practicum infrastructure, causes practicum in schools to not be implemented. The subject of acid-base material which should be in an experiment cannot be applied due to limited indicators. The results of observations in the field showed that students could not distinguish between acidic and basic solutions because they did not get a lesson. Chemistry subject teachers in several high schools in Donggala Regency do not carry out practical work on acid-base materials because they never used natural materials such as flowers as pH paper. Therefore, it is necessary to increase the understanding of teachers regarding the concept of acids and bases and natural materials that can be used as natural indicators to replace synthetic indicators. This service activity was attended by 10 participants consisting of chemistry teachers who are members of the chemistry MGMP of Donggala Regency. Service activities are carried out by understanding the concept of acid-base and the use of natural materials as natural indicators also demonstrating and guidance on making pH paper from natural materials (flowers). This activity provides additional knowledge for teachers in the use of natural materials as a substitute for synthetic indicators in acid-base material practicum so that the quality of learning is expected to increase.